USING INDICATORS TO DETERMINE THE LEVEL OF KNOWLEDGE OF STUDENTS (Academicia Globe: Inderscience Research, 2022)
The article deals with one of the modern methods for assessing the quality of education, the use of a set of indicators (indicators) in the educational process.